2007
DOI: 10.1017/s175173110700064x
|View full text |Cite
|
Sign up to set email alerts
|

Histological characteristics of longissimus dorsi muscle and their correlation with restriction fragment polymorphisms of calpastatin gene in F2 Jinghua × Piétrain crossbred pigs

Abstract: In order to evaluate the genotype of the calpastatin (CAST) gene and its relationship to muscle histology and other post mortem traits in the Jinhua 3 Pié train F 2 pig family, 158 barrows and gilts were electrically stunned and exsanguinated. Both blood and muscle samples were collected, and both post mortem traits and meat qualities were recorded. Restriction fragment length polymorphism (RFLP) analysis, the periodic acid Schiff reaction (PAS) and myosin heavy-chain immunohistochemistry were employed to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These results indicated that the IMF and carcass lean content is not significantly affected by CAST gene expression. Wu et al (2007) found that CAST was significantly correlated with diameter, area, circularity, and the aspect ratio of muscle fiber, but not with carcass lean and IMF content of pigs. Although the association between CAST mRNA expression and meat quality has been reported on cattle and pigs (Chung et al, 2001;Koćwin-Podsiadla et al, 2003), how CAST affects meat quality in other animals and its molecular mechanism need to be further studied.…”
Section: The Relationship Between Gene Expression and Carcass Lean Imf Contentmentioning
confidence: 82%
“…These results indicated that the IMF and carcass lean content is not significantly affected by CAST gene expression. Wu et al (2007) found that CAST was significantly correlated with diameter, area, circularity, and the aspect ratio of muscle fiber, but not with carcass lean and IMF content of pigs. Although the association between CAST mRNA expression and meat quality has been reported on cattle and pigs (Chung et al, 2001;Koćwin-Podsiadla et al, 2003), how CAST affects meat quality in other animals and its molecular mechanism need to be further studied.…”
Section: The Relationship Between Gene Expression and Carcass Lean Imf Contentmentioning
confidence: 82%
“…However, Klosowska et al (2005) concluded on significant associations between CAST_RsaI, another locus in intron 6 of the gene with diameters of fibers and the proportion of fast-twitch fibers in a bundle. Additionally, in F2 Jinhua x Pietrain crossbred pigs, different genotype patterns of CAST polymorphisms (MspI, HinfI and RsaI) are statistically related to loin muscle area (Wu et al, 2007), of which BB/DD/FF pigs provided higher muscle area than those of AB/CD/EF individuals. This difference is probably from the discrepancy between the IIb fiber content of the two animal groups as mentioned by Wimmers et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…This was further supported by Krzęcio et al (2005), who demonstrated the effect of CAST_MspI on drip loss and nutritional value of the meat, that is, protein content. In the Jinhua x Pietrain F2 population, the three genotypes at these loci were proven to associate with loin area and pH 45 min value as well as the percentage of intramuscular connective tissue (Wu et al, 2007). Moreover, the association of CAST_HinfI locus with pork quality traits including pH, drip loss and meat color was reported in a cross of commercial Pietrainbased breed.…”
Section: Introductionmentioning
confidence: 91%